Perceptions of Testicular Cancer and Testicular Self-Examination Among College Men - Michael J. Rovito PhD; Thomas F. Gordon PhD; Sarah Bauerle Bass PhD, MPH; Joseph DuCette PhD (American Journal of Men's Health, 2011)
Testicular self-exam (TSE) is an important tool to prevent late-stage diagnosis of testicular cancer (TC). However, most young men remain unaware of their risk for TC despite a growing number of interventions promoting knowledge and awareness of the disease. Of those interventions, very few discuss perceived vulnerability, perceived value of health promotion, and/or preference for informational materials as viable predictors of behavioral change. In this study, 300 university males were surveyed on their perceptions of vulnerability, perceived value of health promotion methods, TC/TSE knowledge, and preference for health promotional information. The results indicated that men were generally unaware of TC and were unsure of their risk of developing the disease. Participants reported very positive responses to questions about the value of health promotion methods, particularly TSE, and indicated a high intention to perform health promotion behaviors. Most important, participants noted that they preferred personalized, tailored information to learn about TC and TSE. Significant predictors of intention to perform TSE include knowledge and awareness of TC/TSE, perceived value of health promotion, and attitudes. Significant predictors of promotional tool preferences differed among generalized pamphlets, personalized messages, and group training sessions. The authors recommend that researchers tailor promotional messages in TC/TSE awareness campaigns with an individual’s preference for promotional tool.